PID Control of Magnetic Levitation (Maglev) System - Muhammad Arif Seto; Alfian Ma'arif (Peneliti Teknologi Teknik Indonesia, 2023)
Magnetic levitation is a process of drifting or shifting an object with a certain reference, by creating a repulsive force from the gravity of an object caused by an electromagnetic field without noise. In modern times like today, with the density of community activities, especially those living in urban areas, it is necessary to be able to carry out activities efficiently as well as quickly. Therefore, the reason for many people to be able to find an innovative solution to make it easier for humans to carry out their activities. One of the innovations that can be a solution to the limited space and time is in the development of magnetic levitation technology. The system that will be used in controlling this maglev is to use a PID controller. Using this PID control will be tested with several , , and values with a setpoint of 950. At the initial tunning with the values =2, =0.01, and =2. Then in the second test using the values =3, =0.1, and =0.3. Software testing is also carried out using matlab. The exact PID value for controlling an elevated object can be found by changing the value of the , , and values that can be searched through a matlab software in the PID tunner feature, which can then be seen the PID tunning results by analyzing the graph that will be displayed by the PID tunner.